The muffled voices of the insane child - tracing the small voices of early child and adolescent psychiatry - Trine Elisabeth Møbius Sørensen (Social Work & Society, 2023)
This article discusses historical, archival and theoretical material constructed about the children, who were labeld insane in Denmark, across the period of 1900-1930. The article draws the reader's attention to this period to examine the experience of the confined children and the "struggles ... out of which contemporary practices emerged and to show the historical conditions of existence upon which present-day practices depend" (Garland, 2014 p. 373). Through 'historical ethnography', the article traces the voices and the experiences of the child labeled 'insane' and argues that the 'clinical subject' during this time could not speak, except through a patchwork of clinical theories and techniques (Swarz, 2005). The analysis follows the small voices of history and argues that children's statements were muffled by discourses of psychiatry and hospital management (Spivak, 1993). By drawing on theoretical perspectives on subjugation represented by postcolonial historiography (Spivak, 1993), the paper will trace their silenced voices (Hak, 1992) by questioning who was speaking to whom, to what purpose and through which system of representation.